Clinical outcome of sacrospinous fixation following pelvic organ prolapse surgery - Poudel, Sandesh; Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2021)
Aims: To evaluate the midterm outcome of sacrospinous fixation done during surgical management of pelvic organ prolapse. Methods: This was an interview based cross sectional follow up study done among the patients who underwent sacrospinous fixation procedure along with pelvic organ prolapse surgery in Kathmandu Model Hospital and Paropakar Maternity Hospital. This was conducted between 15 th February 2021 and 15 th April 2021. Post-operative cases 22 to 30 months (average 2 years) from the day of surgery were included. Results: Out of 321 eligible SSF patients from both the hospital, 156 agreed to participate. Among them, 77 (48%) were in 60-69 years of age and 82% were postmenopausal; 33% were more than para 3; 20% had right gluteal pain that was decreased to 1.9% by 2 years; and 20% had some degree of urgency and stress incontinence. Conclusion: Sacrospinous fixation is safe and effective procedure which can be done during pelvic organ prolapse surgery with good success rate and minimal post-operative complications.